Population structure, vegetation composition and economic potentials of Parkia timoriana in Meru Betiri National Park, East Java, Indonesia - Anik Nur Hidayati; ERVIZAL A.M. ZUHUD; NURI ANDARWULAN (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Hidayati AN, Zuhud EAM, Andarwulan N. 2020. Population structure, vegetation composition and economic potentials of Parkia timoriana in Meru Betiri National Park, East Java, Indonesia. Biodiversitas 21: 203-210. Kedawung (Parkia timoriana (DC.) Merr.) is one of rare medicinal plant species because it is only found in a small part of Indonesia. P. timoriana has high ecological and economic potential because it contains various active compounds such as anticancer. This study was aimed to investigate the population structure, vegetation community composition, and distribution, as well as the potential production and economic values of P. timoriana in rehabilitation zone in Meru Betiri National Park, East Java, Indonesia. The methods used were vegetation analysis, direct observation, and in-depth interviews with selected respondents using purposive sampling. We found that P. timoriana population at the study sites was only at tree and pole stages, while no sapling and seedling was found. This condition implies that regeneration of P. timoriana at the study sites was not happening which can threaten its sustainability in the future. P. timoriana dominated the vegetation at the studied sites which were indicated by the highest importance value index. Utilization of P. timoriana by the local community was by selling the seeds to medicinal industries or used as herbal medicine. While having conservation values, the management of P. timoriana stands in Andongrejo Resort also had the potential to generate economic values up to 17.6 billion rupiahs. Considering the great economic potential of P. timoriana and to ensure sustainability, so that nursery, breeding and regeneration of P. timoriana should be made in order to obtain the best quality seeds.